Inextensible Flows of Curves on Lightlike Surfaces - Yuzbasi, Zuhal Kucukarslan; Yoon, Dae Won (Mdpi, 2018)
In this paper, we study inextensible flows of a curve on a lightlike surface in Minkowski three-space and give a necessary and sufficient condition for inextensible flows of the curve as a partial differential equation involving the curvatures of the curve on a lightlike surface. Finally, we classify lightlike ruled surfaces in Minkowski three-space and characterize an inextensible evolution of a lightlike curve on a lightlike tangent developable surface.
Keywords: inextensible flow; lightlike surface; ruled surface; Darboux frame